Single crystal growth and physical properties of YbPd2Si2. (18th March 2015) - Matsumoto, Y; Hanya, K; Haga, Y; Fisk, Z; Ohara, S
Abstract: We report the heat capacity and magnetic properties of single crystals of YbPd2 Si2 grown from Sn flux. YbPd2 Si2 is a non magnetic heavy fermion compound with electronic specific heat coefficient γ = 95 mJ/mol K 2 and Pauli paramagnetic susceptibility χ0 = 0.0115 emu/mol. The density of states of single crystal YbPd2 Si2 is approximately half that of polycrystalline YbPd2 Si2 while the strength of the Kondo effect in the single crystal is approximately twice that of poly crystal.